Formation of the River Water Chemistry in the Middle Section of Dousitu River, China - Qian Hui; Li Peiyue; Ding Jia; Yang Chao; Zhang Xuedi (E-Journal of Chemistry)
On basis of hydrogeology of the study area, the characteristics of chemistry of river water and groundwater were analyzed. Analysis results of three river water samples (B3, B4 and B5) collected in the middle section of Dousitu River show the TDS increases from B3 to B4 and decreases from B4 to B5. The concentrations of Cl-, Na+, K+, Mg2+ and HCO3- have a similar change with TDS, but the concentrations of Ca2+ and SO42- increase steadily along flow path. The chemical types of the river water change from HCO3•Cl-Na to Cl•SO4•HCO3-Na and finally to SO4•Cl-Na. The causes of these changes are analyzed and studied in depth using various methods. Results indicate river water evaporation, dissolution/precipitation of minerals, cation exchange and mixing of different waters all play important roles in the formation of the river water chemistry. But in different sections of the river, the main processes are different. The study shows that when a reservoir is built in arid areas, the loss of water resources due to evaporation is huge, which can lead to the degradation of water qualities. Hence, great care should be taken to build a reservoir in arid or semi-arid regions.